A lactam-functionalized copper bent diisophthalate framework displaying significantly enhanced adsorption of CO2 and C2H2 over CH4. Issue 30 (8th July 2019) - He, Minghui; Xia, Fengjie; Xu, Tingting; Gao, Xiaoxia; Jiang, Zhenzhen; Wang, Xia; He, Yabing
Abstract : The first lactam-functionalized MOF based on a bent diisophthalate ligand was constructed, displaying significantly enhanced uptake and selectivity for C2 H2 and CO2 over CH4 . Abstract : The design and construction of porous materials for high-efficient adsorption-based separation of CH4 from C2 H2 and CO2 is a fundamental goal in the chemical industry. In this work, a lactam-functionalized bent diisophthalate linker, 5, 5′-(1-methylpyridin-2(1 H )-one-3, 5-diyl) diisophthalic acid, was judiciously designed and utilized to construct a dicopper paddlewheel-based MOF under solvothermal conditions. Single-crystal X-ray diffraction revealed that the resulting solid is a three-dimensional mfj -type network incorporating Lewis-acidic copper sites and accessible lactam groups as two different kinds of functional sites. Furthermore, gas adsorption studies indicated that the material exhibited great promise for C2 H2 /CH4 and CO2 /CH4 separations. In particular, compared to the unmodified parent compound, the resultant MOF exhibits 9.4% and 12.9% higher C2 H2 and CO2 uptake capacities and 48.0% and 28.3% higher C2 H2 /CH4 and CO2 /CH4 adsorption selectivities for the equimolar gas mixtures at 298 K and 1 atm, despite the lower specific surface area and pore volume. This work reported the first lactam-functionalized MOF displaying significantly enhanced adsorption of CO2 and C2 H2 over CH4 .